1989
DOI: 10.1073/pnas.86.24.9971
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of homeobox-containing genes of the honeybee and Drosophila.

Abstract: We report the isolation of seven homeobox-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 26 publications
0
54
0
Order By: Relevance
“…2F). In situ hybridization for e30 RNA, a honeybee ortholog of engrailed (Walldorf et al, 1989;Dearden et al, 2006) allows better definition of segments (Fig. 2F).…”
Section: Research Article Development 138 (16)mentioning
confidence: 99%
“…2F). In situ hybridization for e30 RNA, a honeybee ortholog of engrailed (Walldorf et al, 1989;Dearden et al, 2006) allows better definition of segments (Fig. 2F).…”
Section: Research Article Development 138 (16)mentioning
confidence: 99%
“…Morphological and classical manipulative studies have been carried out, but studies of gene function or expression are rare. Those studies published have concentrated on genes associated with segmentation (Fleig 1990;Binner and Sander 1997;Osborne and Dearden 2005a), Hox genes (Walldorf et al 1989(Walldorf et al , 2000Fleig et al 1992), and sex-determining genes (Beye et al 2003). Recently techniques for studying honey bee development have become available, including robust methods for studying gene expression patterns (Osborne and Dearden 2005b), RNAi to study gene function in both embryos and adults (Beye et al 2002;Amdam et al 2003), and cell culture protocols (e.g., see Bergem et al 2006).…”
mentioning
confidence: 99%
“…It is interesting to find that the two honeybee en genes do not possess an intron in the homeobox region while their Bombyx and Drosophila counterparts do (13). This intron is also absent in the mouse (16), zebrafish (19), and sea urchin (20).…”
mentioning
confidence: 98%
“…Based on sequence similarity, en homologs have been isolated from many invertebrate and vertebrate species (13)(14)(15)(16)(17)(18)(19)(20)(21). Expression studies revealed that en probably plays a role in neurogenesis (14,18,(21)(22)(23)(24)(25)(26)(27)(28), as has been shown by genetic analysis in Drosophila (4).…”
mentioning
confidence: 99%